Beyond the academic showcase. The issues of the status and mobility of African scholars for African studies conferences held in France - (:unkn) unknown (My University, 2018)
This paper questions social representations and imaginaries, which are embedded in academic practice in the field of African studies in France, by analyzing the preparation of a conference for junior scholars, specialized in Africa and held in France. It discusses the place and the participation of African academics in the structure of this scientific field and the way they influence knowledge production and its circulation. This reflexive critique explores the contrasted outlines of the scientific object that is “Africa,” in terms of its symbolizations, its representativeness, and the episteme that it confronts. The analysis also underlines the social reproduction of several systemic mechanisms, related in particular to the invisibility of African scholars affiliated with African institutions and with the academic filters, which are more than economic or political ones, that can impede their mobility towards France.
Keywords: African Research